UMP, UUM and UiTM researchers study foreign workers management in Malaysia - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 13 July 2022 - A joint group of researchers from three public universities (UA), namely Universiti Malaysia Pahang (UMP), Universiti Utara Malaysia (UUM), and Universiti Teknologi MARA (UiTM), has been entrusted by the Institute of Public Safety of Malaysia (IPSOM) to assist in conducting the study on the Establishment of Specific Entities for the Management of Admission, Issuance, and Termination of Visit Pass (Temporary Employment) or PLKS for foreign workers.